The Possible Role of TLR2 in Chronic Hepatitis B Patients with Precore Mutation - Malihe Moradzadeh; Sirous Tayebi; Hossein Poustchi; Kourosh Sayehmiri; Parisa Shahnazari; Elnaz Naderi; Ghodratollah Montazeri; Ashraf Mohamadkhani (Advances in Virology)
Recognition mechanisms of innate immune response help to improve immunotherapeutic strategies in HBeAg-negative chronic hepatitis B (CHB). Toll-like receptor 2 (TLR2) is an important component of innate immunity. In this study, the frequency of precore mutations of the hepatitis B virus (HBV) and serum TLR2 were evaluated in CHB patients. Fifty-one patients with chronic hepatitis B, negative for HBeAg and detectable HBV DNA, were examined for the presence of mutations in pre-core region of HBV genome by direct sequencing. Serum TLR2 was measured by enzyme-linked immunosorbent assay. Interactions of truncated HBeAg and TLR2 proteins were evaluated with molecular docking software. The G1896A pre-core mutation were detected in 29 (57%) which was significantly associated with higher concentration of serum TLR2 in comparison with patients without this mutation (4.8 ± 2.9 versus 3.4 ± 2.2 ng/mL, P=0.03). There was also a significant correlation between serum ALT and TLR-2 (r=0.46; P=0.01). Docking results illustrated residues within the N-terminus of truncated HBeAg and TLR2, which might facilitate the interaction of these proteins. These findings showed the dominance of G1896A pre-core mutation of HBV variants in this community which was correlated with serum TLR2. Moreover TLR2 is critical for induction of inflammatory cytokines and therefore ALT elevation.